2020
DOI: 10.1080/23746149.2020.1770627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations of amyloid beta assemblies

Abstract: Several neurodegenerative disorders arise from the abnormal protein aggregation in the nervous tissue leading tointracellular inclusions or extracellular aggregates in specific brain areas. In case of Alzheimer Disease, the accumulation of the Amyloid Beta peptide in the brain is proposed to be an early important event in the pathogenesis. Despite significant research efforts in this field, the molecular mechanisms of protein misfolding and aggregation remain somewhat unrevealed.Within this framework, computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 220 publications
(263 reference statements)
1
27
0
Order By: Relevance
“…To integrate the NMR experimental data and to evaluate the stability of the Aβ(1–42) conformation solved in HFIP/water 50/50 v / v when exposed to a complete aqueous system, we performed 50 ns molecular dynamics (MD) calculation starting from the 3D coordinates obtained from NMR spectra assignment. Although aware of the limitations of the traditional computational methods we used, the results are in agreement with those obtained with REMD protocols [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 80%
“…To integrate the NMR experimental data and to evaluate the stability of the Aβ(1–42) conformation solved in HFIP/water 50/50 v / v when exposed to a complete aqueous system, we performed 50 ns molecular dynamics (MD) calculation starting from the 3D coordinates obtained from NMR spectra assignment. Although aware of the limitations of the traditional computational methods we used, the results are in agreement with those obtained with REMD protocols [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 80%
“…Computational biology approaches have proven to be resourceful means to study biomolecular interactions when other methods of structural analysis provide incomplete information [ 12 , 13 , 14 , 15 ]. In the case of Aβ peptides, their lack of intrinsic structure in aqueous media, the fact that they gain different structures when interacting with specific partners, and their overall dynamic nature, makes these molecules very difficult to study using solution-based structural methods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several important intermolecular events involving Aβ, relevant to processes such as folding or binding, occur in a short time scale that is accessible with computational approaches. The complexity in these systems has also been holding back many computational efforts due to difficulties in obtaining adequate sampling [ 13 , 16 ]. Nevertheless, methods such as molecular dynamics (MD) simulations allow us to study the conformational space of many biomolecules at atomic resolution down to the µs timescale [ 13 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Although it is known that 14-3-3 proteins are involved in neurological disorders and the brain is the tissue with most concentration of these proteins, most of the computational studies involve the beta amyloid in comparison of 14-3-3 proteins. [25][26][27] Ingólfsson, et al, 3 recently reported a study of a realistic human brain plasma membrane using advances in computational power and molecular dynamics simulation (MD) techniques.…”
Section: Introductionmentioning
confidence: 99%